POLICY IMPLEMENTATION OF THE FIVE-DAY WORK PROGRAM (LKH) CASE STUDY AT SMP NEGERI 1 PAGUYAMAN - YANTI KADIR ULITOTO; Zuchri Abdussamad; Sri Yulianti Mozin (Jurnal Ilmu Manajemen dan Bisnis, 2021)
The purpose of the research is: 1) To find out and analyze the policy implementation of the five-day work program at SMP Negeri 1 Paguyaman, based on planning, implementation, and evaluation; 2) To find out and analyze the supporting factors; 3) To find out and analyze the inhibiting factors for the implementation of the five-day work program (LHK) at SMP Negeri 1 Paguyaman. This research used a qualitative approach and two types of research data, namely primary data and secondary data. The results showed that the supporting factors for the implementation of the Five Working Days Program (LHK) at SMP Negeri 1 Paguyaman were communication, resources (in this case human resources and infrastructure), disposition, and bureaucratic structure. With these supporting factors, this five-day work program (LHK) can be implemented. Although this program has been implemented, there are several deficiencies in each of the supporting factors, so that, it becomes an obstacle in the implementation of the Five-Days Work Program (LHK) at SMP Negeri 1 Paguyaman.